The Development of Test Instruments to Measure the Science Literation Skills of Junior High School Students in Global Warming Themes (Universitas Negeri Semarang, 2021)
The measurement of scientific literacy is very important to find out the extent to which students have been literate in science. The preparation of test instruments based on scientific literacy is an effort to measure the literacy skills of students in the field of science. The purpose of this research is to develop a valid, practical, and effective science literacy test instrument to measure the scientific literacy skills of students on the theme of global warming. The research method was used Research and Development (R & D) with the research design of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The final product in this research is a scientific literacy-based test instrument to measure the scientific literacy skill of students that have been declared valid and feasible by experts and is valid in the content, in the form of 20 reasonable multiple-choice questions that are tailored to the indicators of the scientific literacy, complete with a grid of questions, answer keys, and bibliography. It can be concluded that the validity of the test instruments received an average percentage of 79.99% and was included in the category of valid and feasible to use. The practicality of the test instrument is in the very practical category seen based on the results of student responses by 87.50% and teacher responses by 94.23%. The effectiveness of the test instrument is in the effective category, since this study can reveal or position the scientific literacy skills of students into three criteria items, namely high, medium, and low, it can be used as input and thought contribution to improve the quality of making the test instruments to measure the skill of scientific literacy on the theme of global warming.